Wastewater Treatment and its Reuse in Jordan - Abu-Awwad, Ahmad M. (Jordan Journal of Agricultural Sciences, 2021)
The prospective agriculture development, in Jordan, is tied up by severe water scarcity that induces imbalances and shortages of water supply for various uses, especially under high population growth rates, natural and non-voluntary migration, and climate change. This paper provides highlights on the wastewater treatment plants (WWTPs) expansion, development, and treated wastewater reuse for the current and past 100 years in Jordan, examples of inefficient utilization of some WWTPs effluent and some of its constituents (such as Nitrogen and Phosphorus). It also suggests the necessary measures in the near future and long-term for the effective use of treated wastewater that improve and increase the reuse of treated wastewater in agricultural irrigation.